Targeting mucosal immunity in malaria control: the underexplored role of IgA - Muwonge, Haruna; Ssewanyana, Isaac; Yeka, Adoke; Byakika-Kibwika, Pauline (Frontiers in Malaria, 2025)
Malaria remains a global health crisis, causing an estimated 263 million cases and 597,000 deaths in 2023. Current measures—including insecticide-treated nets, ACTs, and the RTS,S vaccine—have stalled in reducing mortality, highlighting the need for novel strategies. While studies IgG and IgM have dominated malaria immunology research, recent data reveal a broader role for Immunoglobulin A (IgA). Evidence suggests that IgA can block parasite entry, activate complement, and modulate inflammation, although its protective efficacy has yet to be established. This review synthesizes the emerging literature on sporozoite- and merozoite-specific IgA responses, examines how IgA arises in a “non-mucosal” infection like malaria, and explores vaccine platforms-oral, nasal, or prime-boost-that might harness IgA alongside IgG. We also identify critical gaps in correlating IgA levels with clinical immunity, emphasizing the need for specialized animal models and longitudinal human cohorts. Ultimately, leveraging IgA-driven mucosal immunity could significantly reinforce existing malaria interventions by preventing parasite establishment at mucosal or skin interfaces. By uniting mucosal and systemic immunity, research on IgA-based vaccines promises a next-generation approach to reducing malaria transmission, thereby creating a path towards global eradication.